2019
DOI: 10.3390/pathogens8020083
|View full text |Cite
|
Sign up to set email alerts
|

How Many Mammalian Reovirus Proteins are involved in the Control of the Interferon Response?

Abstract: As with most viruses, mammalian reovirus can be recognized and attacked by the host-cell interferon response network. Similarly, many viruses have developed resistance mechanisms to counteract the host-cell response at different points of this response. Reflecting the complexity of the interferon signaling pathways as well as the resulting antiviral response, viruses can—and often have—evolved many determinants to interfere with this innate immune response and allow viral replication. In the last few years, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…It is encoded by an internal ORF on the bicistronic S1 segment and thus the coding sequences of p13 and σ3 proteins are intrinsically linked. Several of the structural proteins of reoviruses counteract the innate antiviral activity during replication, including the outer structural protein σ3 and λ2 [ 34 ]. However, the analysis of the innate response did not indicate any substantial differences between low-and high-virulent isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It is encoded by an internal ORF on the bicistronic S1 segment and thus the coding sequences of p13 and σ3 proteins are intrinsically linked. Several of the structural proteins of reoviruses counteract the innate antiviral activity during replication, including the outer structural protein σ3 and λ2 [ 34 ]. However, the analysis of the innate response did not indicate any substantial differences between low-and high-virulent isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral responses have reported that the PRV-1 infection of cultured Atlantic salmon red blood cells induces Mx and Protein kinase R (PKR) [29], the latter being a mediator of translational inhibition [30]. In mammalian orthoreovirus (MRV) infected cells, translational shutoff has been demonstrated through PKR and phosphorylation of the eukaryotic translation initiation factor (eIF)-2α, as part of the interferon-regulated antiviral response [31,32]. Further research would provide more insights into the molecular control mechanisms of PRV replication in target cells, and for the persistence of PRV-1 RNA in salmon erythrocytes, a well-suited cell type for long-term viral persistence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inherent advantages in virus replication, it was possible that T3D strains differentially induced host responses and affected virus replication kinetics and oncolytic efficiencies. Indeed, previous studies found differences in interferon responses to distinct reovirus serotypes and lab strains [21][22][23][24][25][26][27]. However, these studies did not investigate the T3D PL strain which is currently in PhaseI/II cancer clinical trials nor compare strains with known differences in in vivo oncolytic activities.…”
Section: Introductionmentioning
confidence: 99%